Formation and photoluminescent properties of nanophotonic elements with nanosized ZnO for smart packaging, deposited by screen printing - Sarapulova, Olha; Sherstiuk, Valentyn (Journal of Print and Media Technology Research, 2023)
Smart food packaging (active and intelligent packaging), which indicates and/or prevents changes in the packaged food product, traces the history of its storage etc., is becoming more popular due to the fact that it enhances safety of packaged food storage, transportation and consumption. It is convenient to use printing techniques to produce active elements of smart packaging, including the elements which respond to the changes in packaged food, which occur as the result of food spoilage or aging. However, issues concerning technological aspects arise when the compositions are printed onto materials such as paper or polymer films, especially if these compositions contain functional nanoparticles with luminescent properties. There has been conducted technological research of formation of luminescent coatings containing nano-sized ZnO, for active and intelligent packaging, using screen printing. Photoluminescent properties of the obtained nanophotonic elements are studied and the factors that affect their properties are defined. It was determined that by manipulating coating thickness, molecular weight of the polymer and the concentration of nanophotonic component in the composition it is possible to increase photoluminescent intensity of the screen-printed coatings and obtain different colors of photoluminescence.